Company Listed on The Indonesian Stock Exchange: Factors That Influence Company Value - Hetharia, Nathanael Bramantya Surya; Siahaan, Magda; Siahaan, Bonar Paul (LPPM Universitas Informatika dan Bisnis Indonesia, 2024)
This research aims to identify the relationship between company size, leverage, managerial ownership, size of the board of directors, cash holding, return on assets, and company age, which influence the value of companies in the manufacturing industry listed on the Indonesian Stock Exchange. The sample for this research uses a purposive sampling method, which uses manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2019. This research data was analyzed using a multiple linear regression model. So, this research shows that leverage and return on assets influence company value. Meanwhile, company size, managerial ownership, board size, cash holding, and company age do not influence company value.